Análise citogenética em espécies de Scinax pertencentes aos clados de S. catharinae e S. ruber, com o uso de técnicas de citogenética clássica e molecular - Oliveira, Gabriela Isabela Gomes de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Scinax genus, which is distributed throughout the American continent from Mexico to Argentina and Uruguay, includes small sized animals known as tree frogs. From the taxonomy point of view, the genus belongs to the Dendropsophini tribe, Hylinae subfamily, Hylidae family and, according to extensive revisions in the family phylogeny, their representatives are currently distributed in two major clades of S. catharinae and S. ruber. The Scinax representatives which had their chromosomes analyzed so far showed 2n = 24, but different karyotypic patterns are observed for each clade, according to the morphology of the first two pairs, Ag-NOR position and the amount of C banded heterochromatin. In this study, we are presenting the cytogenetic data of 11 species of Scinax, three of them analyzed for the first time, five from the clade of S. catharinae (S. albicans, S. argyreornatus, S. hiemalis, S. littoralis and Scinax sp. gr. catharinae) and six from the clade of S. ruber (S. caldarum, S. crospedospilus, S. eurydice, S. fuscovarius, S. hayii and S. similis). The aim was to find new chromosome markers to better characterize both clades. The results of Giemsa staining and Ag-NOR comfirmed the the previous observed patterns for each clade. Replication bands obtained in this work for the species S. hiemalis, S. littoralis, S. crospedospilus, and S. eurydice were compared to those previously obtained in our laboratory for the species S. fuscovarius and S. similis, allowing to confirm that the observed differences with the use of conventional staining among species of distinct clades seem to be due to deletions on the short arms of chromosomes from pairs 1 and 2. The remaining chromosomes especially those of large size showed equivalent banding patterns. The C banding technique revealed on both clades subtle small bands, which only in S. crospedospilus, S. hayii, and S. littoralis appeared marked with...

O gênero Scinax, que está distribuído no continente americano desde o México até a Argentina e Uruguai, inclui animais de tamanho pequeno conhecidos como pererecas. Do ponto de vista da taxonomia, o gênero pertence à tribo Dendropsophini, subfamília Hylinae, família Hylidae e, de acordo com as extensas revisões na filogenia da família, seus representantes estão atualmente distribuídos nos dois grandes clados de S. catharinae e S. ruber. As espécies de Scinax que tiveram seus cromossomos analisados apresentaram 2n=24, mas padrões cariotípicos distintos são observados para cada clado, de acordo com a morfologia dos dois primeiros pares, posição da Ag-RON e quantidade de heterocromatina identificada por bandamento C. No presente trabalho, são apresentados dados citogenéticos de 11 espécies de Scinax, três delas analisadas pela primeira vez, totalizando cinco representantes do clado de S. catharinae (S. albicans, S. argyreornatus, S. hiemalis, S. littoralis e Scinax sp. gr. catharinae) e seis do clado de S. ruber (S. caldarum, S. crospedospilus, S. eurydice, S. fuscovarius, S. hayii e S. similis). O objetivo da análise foi encontrar novos marcadores cromossômicos para melhor caracterizar ambos os clados. Os resultados de coloração convencional e Ag- RON confirmaram os padrões observados anteriormente para cada clado. As bandas de replicação obtidas no presente trabalho para as espécies S. hiemalis, S. littoralis, S. crospedospilus e S. eurydice foram comparadas àquelas já obtidas anteriormente em nosso laboratório para as espécies S. similis e S. fuscovarius, possibilitando confirmar que as diferenças observadas em coloração convencional entre as espécies de clados distintos parecem ser decorrentes de deleções nos braços curtos dos cromossomos dos pares 1 e 2. Os demais cromossomos especialmente aqueles de tamanho grande mostraram correspondência nos padrões de...
Keywords: Genetica animal; Citogenética animal; Hylidae; Cromossomos